LACTOBACTERIA IN FOOD: THEORETICAL BASIS AND PRACTICAL MEANING (BY EXAMPLE OF LACTOBACILLUS RHAMNOSUS GG) - S.V. Belmer (Вопросы современной педиатрии, 2011)
Normal intestinal microflora is necessary for human health. Sour milk products influence the composition and functional state of intestinal micro flora. Multiple studies showed high probiotic activity of Lactobacillus rhamnosus GG (ATCC 53103, LGG) and its safety in children and adults. LGG has beneficial effect on functional disorders of intestinal motor function, and in treatment of allergic and inflammatory diseases. These effects are realized through TLR2 receptors activating NFkB-mediated signal way and regulating cytokines synthesis. Besides, LGG blocks interaction of mast cells and IgE and favors to the expression of H4 histamine receptors. LGG (ATCC 53103) are included in liquid yoghurts («Tyoma» for children from 8 months old), kefir, tan, cottage cheese and other food produced by Bio Balance.Key words: children, nutrition, Lactobacillus rhamnosus GG, probiotics, sour milk products, food allergy.(Voprosy sovremennoi pediatrii — Current Pediatrics. 2011; 10 (3): 80–85)